Can Cellphone Shutdowns Stop Terrorist Violence? Evidence from Pakistan - Mustafa, Fatima (Terrorism and political violence, 2023)
While there has been growing concern about the use of technology by terrorist groups to organize and execute violence, there has been much less academic work on the effectiveness of governmental efforts to control the use of technology to prevent terrorist violence. Governments across the world have relied on network shutdowns to tackle violence, amongst other ends. Using data from one such country, Pakistan, this paper examines the effectiveness of disrupting cellphone networks as acounterterrorism strategy to tackle terrorist violence. This paper relies on daily data on terrorist violence in Pakistan from January 2012 to December 2017 combined with data on government-mandated cellphone shutdowns. The results show a statistically significant decline in the number of terrorist attacks on the day of cellphone shutdowns and an increase in terrorist attacks on the day after cellphone shutdown. Overall, it is argued that while cellphone shutdowns might displace terrorist violence from one day to the next, they are not an effective way to tackle terrorist violence.